Influences on contraceptive method choice among adolescent women across urban centers in Nigeria: a qualitative study - Elynn Kann Sanchez; Courtney McGuire; Lisa M. Calhoun; Gwyn Hainsworth; Ilene S. Speizer (BMC, 2021)
Abstract Background Despite calls to increase contraceptive use among adolescents and youth, large gaps still exist, creating an unmet need for family planning. Past research has focused on barriers to seeking a method. There is less understanding of the types of methods young women want and who and what influences these decisions. This study examines what method characteristics young Nigerian women prioritize when choosing a method to inform future family planning programming. Methods In 2018, eight focus group discussions (FGD) were conducted in the Nigerian cities of Ilorin and Jos with 83 young women ages 15-24. Participants were identified by community contacts and separated into groups by religion and marital status. The discussion guide utilized a vignette structure to understand the participants' perceptions on contraceptive behavior and attitudes and misconceptions surrounding different types of methods. The FGDs were undertaken and analyzed by collaborative teams from the University of Ibadan and the University of North Carolina-Chapel Hill. A thematic analysis of the transcripts was performed using Atlas.ti, including two rounds of coding, and multiple reviews by the research team. Results The method characteristics associated with young women's contraceptive decisions include: side effects, reliability, length of coverage, privacy, cost, and accessibility. Side effects, reliability, and privacy were described as negatively linked to short-acting methods whereas easy accessibility and low cost were positive characteristics of these methods. Long-acting methods were generally viewed as positive. Participants' focus on side effects commonly resulted from concerns about the impact on future fertility. The characteristics prioritized by individuals change throughout their adolescence and as their marital status changes. Providers, peers, parents, and partners were all found to have an influence over method choice in different ways. The role of these influencers also changes over the adolescent years. Conclusion This study demonstrates that programs should prioritize expanding method choice to increase the number of available options to ensure all young women can access a method that fits their desired method characteristics. Programming should ensure that medically accurate information is widely distributed to harness providers, peers, parents and partners as a resource for information about specific methods.